ANALISA FAKTOR KARAKTERISTIK ENTREPRENEUR, KARAKTERISTIK SUMBER DAYA MANUSIA, DAN KARAKTERISTIK UMKM TERHADAP PERKEMBANGAN USAHA DENGAN INOVASI SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Pedagang grosir dan retail di Pasar Genuk - Semarang) - Azis Fathoni (Jurnal Ekonomi dan Bisnis Kontemporer, 2015)
This research intends to find out the effect of characteristic of entrepreneur, characteristic ofhuman resource management, SMEs characteristics to the innovation effort and development ofbusiness. The study was conducted in Semarang city, the sample were 42 merchants who haveemploy a labor work as two year experience at Genuk market. The research type is explanatoryresearch. Data analysis using linear regression. The results showed that EntrepreneurCharacteristics, Human Resource Management Characteristics and SMEs Characteristic eitherpartially or simultaneously have an influence on the innovating and Development Of Business InTraditional Markets of Genuk. Charctersitic of entrepreneur is the most influencing variable tothe innovating and to Development Of Business. Recommendation for trader in the traditionalmarket is they need to always foster an optimistic attitude in running the business. This attitudecan be formed by creating a bevy of fellow traders so that every issue can be resolved soon.Besides the characteristic form of motivation to strive entrepreneur must be maintained byattending various training such as retail training in financial management, merchandisearrangements that will grow the innovation and creativity that never died for businessdevelopment.Keyword:Entrepreneur Characteristics, Human Resource Management Characteristic, Characteristics Of SMEs,Innovation, Development Business.